Shorter High-Intensity Cycling Intervals Reduce Performance and Perceived Fatigability at Work-Matched but Not Task Failure. Issue 4 (5th April 2023) - MCCLEAN, ZACHARY; IANNETTA, DANILO; MACINNIS, MARTIN; ABOODARDA, SAIED JALAL
ABSTRACT: Introduction: The intensity, duration, and distribution of work and recovery phases during high-intensity interval training (HIIT) modulate metabolic perturbations during exercise and subsequently influence the development of performance fatigability and exercise tolerance. This study aimed to characterize neuromuscular, perceptual, and cardiorespiratory responses to work-to-rest ratio-matched HIIT protocols differing in work and rest interval duration. Methods: Twelve healthy individuals (six women) first completed a ramp incremental test to determine 90% of peak power output, and then in three randomized visits, they completed three cycling protocols to task failure at 90% of peak power output: (i) 3- to 3-min work-to-passive rest ratio HIIT (HIIT3min ), (ii) 1- to 1-min work-to-passive rest ratio HIIT (HIIT1min ), and (iii) constant load (CL). Interpolated twitch technique, including maximal voluntary isometric knee extensions and femoral nerve electrical stimuli, was performed at baseline, every 6 min of work, and task failure. Perceptual and cardiorespiratory responses were recorded every 3 min and continuously across the exercises, respectively. Results: The work completed during HIIT1min (8447 ± 5124 kJ) was considerably greater than HIIT3min (1930 ± 712 kJ) and CL (1076 ± 356) ( P < 0.001). At work-matched, HIIT1min resulted in a lesser decline in maximal voluntary contraction and twitch force compared with HIIT3min and CL ( P < 0.001). Perceived effort, pain, and dyspnea were least in HIIT1min and HIIT3min compared with CL ( P < 0.001). At task failure, HIIT1min resulted in less voluntary activation than HIIT3min ( P = 0.010) and CL ( P = 0.043), and engendered less twitch force decline than CL ( P = 0.021). Conclusions: Overall, the mitigated physiological and perceptual responses during shorter work periods (HIIT1min ) enhance exercise tolerance in comparison to longer work intervals at the same intensity (HIIT3min, CL).